ROLE OF OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY IN DETECTING AND MONITORING INFLAMMATORY CHOROIDAL NEOVASCULARIZATION. Issue 6 (June 2022) - Kongwattananon, Wijak; Grasic, David; Lin, Henry; Oyeniran, Enny; Sen, H. Nida; Kodati, Shilpa
Abstract : Optical coherence tomography angiography is effective in detecting active inflammatory choroidal neovascularization in heterogenous uveitic etiologies. Optical coherence tomography angiography provides detailed visualization of inflammatory choroidal neovascularization including morphologic features, location, and neovascular flow. In addition, optical coherence tomography angiography can also be used as an adjunct to monitor treatment response of inflammatory choroidal neovascularization. Abstract : Purpose: To investigate the utility of optical coherence tomography angiography (OCTA) for the detection of inflammatory choroidal neovascularization (iCNV) and monitoring their response to treatment. Methods: A retrospective review of patients with a diagnosis of uveitis and associated iCNV with active exudation was performed. Active iCNV was determined by spectral domain OCT and/or fluorescein angiogram. Spectral domain OCTA outer retina to choriocapillaris slabs was evaluated for the presence of iCNV. Follow-up OCTA images were qualitatively assessed to determine whether regression of iCNV occurred after treatment. Results: Thirteen eyes of 12 patients were included. The etiologies of uveitis include punctate inner choroidopathy (n = 4), multifocal choroiditis (n = 2), presumed sarcoid uveitis (n = 2), tuberculous choroiditis (n = 1), birdshot chorioretinopathy (n = 1), syphilitic uveitis (n = 1), serpiginous choroiditis (n = 1), and idiopathic panuveitis (n = 1). Inflammatory choroidal neovascularization was detected on en face OCTA in 10 of 13 eyes (76.9%). After iCNV treatment, en face OCTA demonstrated complete regression of iCNV in 5 of 10 eyes (50%), partial regression in 2 of 10 eyes (20%), and no regression in 3 of 10 eyes (30%). Conclusions: Optical coherence tomography angiography is an effective modality for detecting iCNV and could provide detailed visualization regarding location, morphologic structure, and flow of the iCNV and its response to therapy.